Effect of pyrolysis temperatures and times on the adsorption of cadmium onto orange peel derived biochar. Issue 2 (February 2016) - Tran, Hai Nguyen; You, Sheng-Jie; Chao, Huan-Ping
The mechanism and capacity of adsorption of cadmium (Cd) on orange peel (OP)-derived biochar at various pyrolysis temperatures (400, 500, 600, 700 and 800°C) and heating times (2 and 6 h) were investigated. Biochar was characterized using proximate analysis, point of zero charge (PZC) analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction. Equilibrium and kinetic experiments of Cd adsorption on biochar were performed. The results indicated that the pH value at PZC of biochar approached 9.5. Equilibrium can be reached rapidly (within 1 min) in kinetic experiments and a removal rate of 80.6–96.9% can be generated. The results fitted the pseudo-second-order model closely. The adsorption capacity was estimated using the Langmuir model. The adsorption capacity of Cd on biochar was independent of the pyrolysis temperature and heating time ( p >0.01). The maximum adsorption capacity of Cd was 114.69 (mg g −1 ). The adsorption of Cd on biochar was regarded as chemisorption. The primary adsorption mechanisms were regarded as Cπ–cation interactions and surface precipitation. Cadmium can react with calcite to form the precipitation of (Ca, Cd)CO3 on the surface of biochar. The OP-derived biochar can be considered a favourable alternative and a new green adsorbent for removing Cd 2+ ions from an aqueous solution.